Seroprevalence and biochemical parameters among patients with Chikungunya in Adamaoua region, Cameroon: A cross‐sectional study - Lise Paule Djamko Toko; Borris Rosnay Galani Tietcheu; Ilyassa Dieudonné Tembar; Pascal Dieudonne Chuisseu Djamen; Nicolas Njintang Yanou (Wiley, 2024)
Abstract Background Chikungunya virus (CHIKV) infection is a vector‐borne febrile illness endemic to Africa. In Cameroon, few studies have documented human exposure to CHIKV, especially in the Adamaoua region. This study aimed to assess the CHIKV seroprevalence in Ngaoundere city and analyze likely association with social, clinical, and biochemical determinants. Methods A cross‐sectional study was conducted at the Ngaoundere Regional Hospital from July to October 2022. The sociodemographic and clinical informations of participants were recorded using a standardized questionnaire. Then, blood tests were performed to determine the CHIKV status, the transaminase, and lipid profiles. Results Of the 200 persons surveyed, 21.5% (43) were positive for anti‐CHIKV IgM antibodies. Age, sex, occupation, marital status, level of study, and place of residence were not significantly associated with CHIKV. However, fever (RR = 4.19; 42.86%; p = 0.0124), headaches (RR = 4.89; 50%; p = 0.0007), digestive disorders (RR = 6.52; 66.67%; p = 0.0001), and the presence of at least two clinical symptoms (RR = 2.55; 26.09%; p = 0.009) were significantly correlated with the presence of CHIKV compared with the absence of clinical symptoms (RR = 1, 10.23%). Similarly, cases of CHIKV were significantly more important in subjects with high aspartate aminotransferase (AST) than in those with normal AST (RR = 2.45; 37.50% vs. 15.28%; p = 0.0006). No significant association was found between alanine‐aminotransferase and lipid profile markers. Conclusion Ngaoundere populations seem to be commonly infected with CHIKV, increasing the incidence of febrile symptoms and transaminase elevation. Clinical and metabolic monitoring is required.